2017
DOI: 10.4103/jfmpc.jfmpc_100_17
|View full text |Cite
|
Sign up to set email alerts
|

A study of emotional intelligence and perceived parenting styles among adolescents in a rural area in Karnataka

Abstract: Context:Adolescence is the time which is crucial for the overall development of a person both mentally and physically. In this period, along with academic intelligence, emotional intelligence (EI) also plays an equal or strong role in student life.Aims:This study was to assess EI, parental bonding, and their association among adolescents in high schools under Sarjapur PHC area.Subjects and Methods:This was a cross-sectional study conducted among high school students under Sarjapur PHC area. The EI was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
(15 reference statements)
2
10
0
1
Order By: Relevance
“…Majority of the participants fall within low and average emotional intelligence. This is similar to finding on adolescent in rural Indian community [26] who reported that students in rural communities had low EI in the domain of selfawareness, motivation, and social skills. The result of this study revealed that composite parenting style is a strong independent predictor of Emotional Intelligence among the participants.…”
Section: Discussionsupporting
confidence: 89%
“…Majority of the participants fall within low and average emotional intelligence. This is similar to finding on adolescent in rural Indian community [26] who reported that students in rural communities had low EI in the domain of selfawareness, motivation, and social skills. The result of this study revealed that composite parenting style is a strong independent predictor of Emotional Intelligence among the participants.…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, low school adjustment was related to the lowest levels of environmental (cognitive and emotional) empathy and connectedness to nature. These results lead us to believe that other relevant variables related to psychosocial processes that enhance school adjustment would presumably also play this role in environmental empathy (cognitive and emotional) and connectedness to nature, such as family relations, parental socialization, communication, family functioning (García, Serra, Zacarés, & García, 2018;George et al, 2017;Rodríguez-Gutiérrez, Martin-Quintana, & Cruz-Sosa, 2016), and peer relations (Farley & Kim-Spoon, 2017;Mavroveli, Petrides, Rieffe, & Bakker, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies showed the reverse relationship of family size with emotional intelligence which was not significant in this study. 30,31 This factor can be explained by the fact of less interaction and supervision from parents in a large family structure.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that there is no gender difference in EI which is consistent with a study done in Shimla, Hyderabad, and Karnataka. [31][32][33] However, many studies, showed that there is a significant difference between genders in case of EI. 34,35 Few showed girls at a higher level of emotional intelligence due to the capability of being more sensitive to emotions, more awareness of their feelings, proficiency in managing their and other's feeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation